High-strength degradable plastic film composition and preparation method and application thereof

CN117229617BActive Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210641399.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-07
Publication Date
2026-10-20
Estimated Expiration
2042-06-07

AI Technical Summary

Technical Problem

[0006]为此,本发明所要解决的技术问题在于提供一种高强度降解塑料薄膜组合物,以解决现有技术中掺杂淀粉原料影响可降解塑料制品强调的问题;

Benefits of technology

[0039]本发明所述高强度降解塑料薄膜组合物,基于上述各原料组分的协同作用,不仅解决了传统淀粉分散性不理想的问题,同时有效改善了可降解薄膜材料的强度性能,大大提高了材料的性能,达到提高材料强度的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003682292010000061
    Figure BDA0003682292010000061
  • Figure BDA0003682292010000071
    Figure BDA0003682292010000071
  • Figure BDA0003682292010000072
    Figure BDA0003682292010000072
Patent Text Reader

Abstract

The application belongs to the technical field of polymer degradable plastics, and particularly relates to a high-strength degradable plastic film composition, and further discloses a preparation method and application thereof. The high-strength degradable plastic film composition disclosed by the application takes PBS, PPC, polycaprolactone, light-proof low-temperature-resistant auxiliary agent, crosslinking agent and plant modified starch as raw materials, and based on the synergistic effect of the above raw material components, not only the problem of unsatisfactory dispersibility of traditional starch is solved, but also the strength performance of the degradable film material is effectively improved, the performance of the material is greatly improved, and the purpose of improving the material strength is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer degradable plastics technology, specifically relating to a high-strength degradable plastic film composition, and further disclosing its preparation method and application. Background Technology

[0002] In today's society, while plastic products bring convenience, the resulting "white pollution" is becoming increasingly serious. Currently, many countries have banned the use of non-degradable products such as plastic bags and plastic mulch films. However, biodegradable plastic bags have now been developed on the market as alternatives.

[0003] Traditional biodegradable plastic products are mostly synthesized using chemical methods. However, raw materials used in chemical synthesis, such as polylactic acid (PLA), polybutylene succinate (PBS), and polybutylene adipate / terephthalate (PBAT), are expensive. To reduce costs, 20-30% starch or calcium carbonate is often added. Because starch has a low density and can improve the puncture resistance of plastic films, it is often used as a primary substitute raw material in biodegradable plastic products. However, starch itself has low strength and poor bonding with polyester plastics; adding large amounts of starch significantly reduces the strength of blown films. Studies have shown that when starch content reaches 30%, the tensile strength of biodegradable plastic films is only 10-12 MPa. Therefore, starch needs to be modified to improve the strength properties of plastic products.

[0004] Currently, there are many reports on starch modification treatments, such as cross-linked starch, modified starch, and oxidized starch, all of which impart special properties to starch by altering its characteristics. However, these traditional modification methods only target the properties of starch itself, slightly improving the bonding between starch and plastics, without substantially changing the mechanical properties of the plastic materials. Moreover, it is difficult to achieve uniform dispersion of modified starch in the material.

[0005] Therefore, improving and optimizing the performance of biodegradable plastic products through the rational treatment of starch is of positive significance for the development and application of biodegradable plastic products. Summary of the Invention

[0006] Therefore, the technical problem to be solved by the present invention is to provide a high-strength degradable plastic film composition to solve the problem that the doping of starch raw materials affects the degradable plastic products in the prior art;

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned high-strength degradable plastic film composition and its application.

[0008] To solve the above-mentioned technical problems, the present invention provides a high-strength degradable plastic film composition comprising the following raw materials in parts by weight: PBS 20-30 parts by weight, polycaprolactone 20-25 parts by weight, PPC 50-70 parts by weight, crosslinking agent 0.5-1.5 parts by weight, plant-modified starch 20-30 parts by weight, and light-shielding and low-temperature resistant additive 3-5 parts by weight.

[0009] Preferably, the high-strength degradable plastic film composition comprises the following raw materials in parts by weight: 22-30 parts by weight of PBS, 20-25 parts by weight of polycaprolactone, 58-70 parts by weight of PPC, 0.6-1.5 parts by weight of crosslinking agent, 20-30 parts by weight of plant-modified starch, and 3-5 parts by weight of light-shielding and low-temperature resistant additive.

[0010] Specifically, the plant-modified starch is modified according to the following preparation method:

[0011] (a) Starch is mixed with water to prepare a starch emulsion. The starch is then heated and the pH of the emulsion is adjusted to be alkaline to perform surface-active treatment.

[0012] (b) Add oxalic acid and cross-linking agent to the above emulsion in sequence to carry out the reaction, collect the reaction products, and obtain modified starch containing double bonds in the molecule;

[0013] (c) The modified starch and the dispersant are thoroughly mixed to obtain the modified starch with the desired high dispersibility.

[0014] Specifically, in step (a), the mass concentration of the starch emulsion is 30-50 wt%.

[0015] The heating step is controlled at a temperature of 50±5℃.

[0016] In step (b), the amount of oxalic acid added accounts for 15-20 wt% of the amount of starch used;

[0017] The amount of the crosslinking aid added is 20-30 wt% of the amount of starch used.

[0018] Specifically, in step (b), the crosslinking aid comprises a mixture of sodium trimetaphosphate and acetic anhydride;

[0019] Preferably, the mass ratio of sodium trimetaphosphate to acetic anhydride is 1:15-30.

[0020] Specifically, in step (c), the dispersant includes polyethylene glycol laurate;

[0021] The amount of the dispersant added is 2-4 wt% of the amount of starch used.

[0022] Specifically, in the high-strength degradable plastic film composition:

[0023] The crosslinking agent includes diethylaminoethanol;

[0024] The light-shielding and low-temperature resistant additive comprises a mixture of hexamethylphosphotriamide and dioctyl sebacate (DOS). Preferably, the ratio of the two is hexamethylphosphotriamide:DOS = 1:10-15. The light-shielding and low-temperature resistant additive not only controls the degradation rate but also further improves the processing performance of the composition and enhances the low-temperature resistance of the composition.

[0025] The PBS is polybutylene succinate with a number-average molecular weight between 30,000 and 40,000.

[0026] The polycaprolactone has an average molecular weight of 10,000-20,000 and is a soft elastomer used as a toughening modifier for the base resin.

[0027] The PPC is polypropylene carbonate, which is polymerized from carbon dioxide and propylene oxide, with a molecular weight distribution of 3-6, and a carbon dioxide content of more than 40%.

[0028] The organic dispersant is polyethylene glycol laurate, which belongs to the fatty acid polyethylene glycol ester series. It can quickly and uniformly disperse starch into the polymer matrix during the material extrusion process, and the dispersant itself has good compatibility with the matrix material.

[0029] The present invention also discloses the use of the high-strength degradable plastic film composition in the preparation of high-strength degradable plastic film materials and the use of high-strength degradable plastic films.

[0030] The present invention also discloses a high-strength degradable plastic film material, which is prepared from the high-strength degradable plastic film composition as raw material.

[0031] The present invention also discloses a method for preparing the high-strength degradable plastic film material, comprising the steps of taking selected amounts of PBS, PPC, polycaprolactone, light-shielding and low-temperature resistant additives, crosslinking agent, and plant-modified starch and mixing them evenly, and the step of performing micro-crosslinking reactive extrusion on the resulting mixture.

[0032] Specifically, the micro-crosslinking reactive extrusion step is performed using a twin-screw extruder;

[0033] The temperature of the twin-screw extruder is controlled at 170-200℃, the feeding speed is 15-25 r / min, and the main extruder speed is 85-100 r / min.

[0034] The high-strength degradable plastic film composition of this invention uses PBS, PPC, polycaprolactone, light-shielding and low-temperature resistant additives, crosslinking agents, and plant-modified starch as raw materials, wherein...

[0035] The plant starch undergoes special modification treatment, giving the starch molecules the characteristics of monomers containing double bonds. Under the action of a crosslinking agent, the modified plant starch can undergo grafting and chain extension reactions in a twin-screw extruder, thereby uniformly dispersing the starch onto the polyester molecular chain through monomer grafting, making it an integral part of the matrix resin. This reduces the impact of starch on the resin's strength, greatly improves the material's performance, and achieves the goal of improving the material's strength.

[0036] The use of the organic dispersant enables the rapid and uniform dispersion of starch in the matrix resin, thereby improving the blown film processing performance of the composition.

[0037] The addition of polycaprolactone of a certain molecular weight, combined with modified PBS and PPC resin, improves the toughness and film-forming properties of the composition.

[0038] The use of light stabilizer complexes effectively controls the degradation rate of the composition and greatly improves its low-temperature resistance.

[0039] The high-strength degradable plastic film composition of the present invention, based on the synergistic effect of the above-mentioned raw material components, not only solves the problem of unsatisfactory dispersibility of traditional starch, but also effectively improves the strength performance of degradable film materials, greatly improving the material performance and achieving the purpose of improving material strength. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0041] Preparation Example 1

[0042] The modified plant starch described in this preparation example was prepared according to the following method:

[0043] (1) Weigh 100g of starch accurately using a balance and place it in a two-necked flask. Add distilled water to prepare a starch emulsion of 40wt%. Stir well and heat in a water bath for 5 minutes. Control the water bath temperature at 50℃. Slowly add sodium hydroxide to adjust the pH of the emulsion and keep it at 9 in order to perform surface activity treatment on the starch.

[0044] (2) Then slowly add oxalic acid (18g), stir continuously in a water bath to keep the temperature uniform, and then slowly add a crosslinking aid solution containing a mixture of sodium trimetaphosphate and acetic anhydride (26g) (the mass ratio of sodium trimetaphosphate to acetic anhydride is 1:25). React for 2 hours. After the reaction is completed, collect the reaction product and filter, wash, dry and crush it to finally obtain a modified starch sample containing acetic anhydride in the molecule.

[0045] (3) The modified starch sample containing acetic anhydride was thoroughly mixed with polyethylene glycol laurate (3g) in a mixer to obtain plant modified starch with high dispersibility, which was then set aside.

[0046] Preparation Example 2

[0047] The modified plant starch described in this preparation example was prepared according to the following method:

[0048] (1) Weigh 100g of starch accurately using a balance and place it in a two-necked flask. Add distilled water to prepare a starch emulsion of 30wt%. Stir well and heat in a water bath for 5 minutes. Control the water bath temperature at 40℃. Slowly add sodium hydroxide to adjust the pH of the emulsion and keep it at 9 in order to perform surface activity treatment on the starch.

[0049] (2) Then slowly add oxalic acid (15g), stir continuously in a water bath to keep the temperature uniform, and then slowly add a crosslinking aid solution containing a mixture of sodium trimetaphosphate and acetic anhydride (20g) (the mass ratio of sodium trimetaphosphate to acetic anhydride is 1:15). React for 2 hours. After the reaction is completed, collect the reaction product and filter, wash, dry and crush it to finally obtain a modified starch sample containing acetic anhydride in the molecule.

[0050] (3) The modified starch sample containing acetic anhydride was thoroughly mixed with polyethylene glycol laurate (2g) in a mixer to obtain plant modified starch with high dispersibility, which was then set aside.

[0051] Preparation Example 3

[0052] The modified plant starch described in this preparation example was prepared according to the following method:

[0053] (1) Weigh 100g of starch accurately using a balance and place it in a two-necked flask. Add distilled water to prepare a starch emulsion of 50wt%. Stir well and heat in a water bath for 5 minutes. Control the water bath temperature at 55℃. Slowly add sodium hydroxide to adjust the pH of the emulsion and keep it at 9 in order to perform surface activity treatment on the starch.

[0054] (2) Then slowly add oxalic acid (20g), stir continuously in a water bath to keep the temperature uniform, and then slowly add a crosslinking aid solution containing a mixture of sodium trimetaphosphate and acetic anhydride (30g) (the mass ratio of sodium trimetaphosphate to acetic anhydride is 1:30). React for 2 hours. After the reaction is completed, collect the reaction product and filter, wash, dry and crush it to finally obtain a modified starch sample containing acetic anhydride in the molecule.

[0055] (3) The modified starch sample containing acetic anhydride was thoroughly mixed with polyethylene glycol laurate (4g) in a mixer to obtain plant modified starch with high dispersibility, which was then set aside.

[0056] Examples 1-6

[0057] In Examples 1-6 below, the amounts of each raw material component are shown in Table 1.

[0058] In the following embodiments of the present invention:

[0059] PBS is produced by Xinjiang Lanshan Tunhe Polyester Co., Ltd., with a density of 1.25±0.05, a melting point of 115℃, and a number-average molecular weight between 30,000 and 40,000.

[0060] The PPC (polypropylene carbonate) is polymerized from carbon dioxide and propylene oxide, with a molecular weight distribution of 3-6, and a carbon dioxide content of more than 40%.

[0061] Polycaprolactone, grade PCL-05, manufactured by Changchun Hanggai Technology Co., Ltd., has a molecular weight of 11,000.

[0062] The modified starch was prepared using the plant-based modified starch obtained in Preparation Example 1 above;

[0063] The crosslinking agent is diethylaminoethanol;

[0064] The light-shielding and low-temperature resistant additive is a mixture of hexamethylphosphotriamide and dioctyl sebacate (DOS) in a mass ratio of 1:12.

[0065] Table 1. Formulation composition (parts by weight) of Examples 1-6

[0066]

[0067]

[0068] The preparation method of the high-strength degradable plastic film described in Examples 1-6 of the present invention is as follows:

[0069] (1) First, dry PBS and PPC in an oven at 80-90℃ for 3 hours, then take them out for later use;

[0070] (2) Weigh the dried PBS and PPC according to the proportion, and then add the polycaprolactone, light stabilizer complex, diethylaminoethanol and plant modified starch according to the proportion. Add them to the mixer and stir at high speed until the materials are completely mixed and uniform. The time is 5 minutes, and then release the materials.

[0071] (3) The mixed materials are fed into a twin-screw extruder for micro-crosslinking reactive extrusion. The temperature of the twin-screw extruder is 190℃, the feeding speed is 20r / min, and the main machine speed is 90r / min. After cooling and pelletizing, the resulting pellets are ready for use.

[0072] (4) The obtained granules are blown into a film with a thickness of 0.010 mm at 185°C.

[0073] Comparative Examples 1-3

[0074] In the following comparative examples 1-3, the amounts of each raw material component are shown in Table 2, and the preparation method of the thin film is the same as that in Examples 1-6.

[0075] Specifically, compared with Example 3, Comparative Example 1 did not add the plant-modified starch described in this invention, but only ordinary modified starch, and the other components were the same; compared with Example 3, Comparative Example 2 did not add the light-blocking and low-temperature resistant additive, but only a general light stabilizer, and the other components were the same; compared with Example 3, Comparative Example 3 did not use a crosslinking agent, and the other components were the same; the other components were the same.

[0076] Table 2 shows the formulation composition (parts by weight) for Comparative Examples 1-4.

[0077]

[0078]

[0079] Experimental Example

[0080] The performance of the films prepared in Examples 1-6 and Comparative Examples 1-3 were tested respectively, and the results are shown in Tables 3-4 below.

[0081] Table 3. Results of thin film performance tests in Examples 1-6

[0082]

[0083] Note: Tensile strength and elongation at break were tested in accordance with GB / T1040-2006.

[0084] Table 4. Performance test results of comparative examples 1-3.

[0085]

[0086] Note: Tensile strength and elongation at break were tested in accordance with GB / T1040-2006.

[0087] As can be seen from the data in Tables 3-4 above, the plastic film prepared by the high-strength degradable plastic film composition of the present invention has significantly better strength properties than the comparative scheme, and the application performance of the film product is better.

[0088] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A high-strength degradable plastic film composition, characterized in that, The raw materials include the following parts by weight: PBS 20-30 parts by weight, polycaprolactone 20-25 parts by weight, PPC 50-70 parts by weight, crosslinking agent 0.5-1.5 parts by weight, plant modified starch 20-30 parts by weight, and light-shielding and low-temperature resistant additive 3-5 parts by weight; wherein, the light-shielding and low-temperature resistant additive is a mixture of hexamethylphosphotriamide and DOS, and the ratio of the two is hexamethylphosphotriamide:DOS=1:10-15; The modified plant starch is prepared according to the following method: (a) Starch is mixed with water to prepare a starch emulsion. The starch is then subjected to surface activity treatment by heating and adjusting the pH of the emulsion to make it alkaline. (b) Add oxalic acid and cross-linking agent to the above emulsion in sequence to carry out the reaction, collect the reaction products, and obtain modified starch containing double bonds in the molecule; (c) The modified starch and the dispersant are thoroughly mixed to obtain the modified starch with the desired high dispersibility. In step (b), the crosslinking aid comprises a mixture of sodium trimetaphosphate and acetic anhydride; the mass ratio of sodium trimetaphosphate to acetic anhydride is 1:15-30.

2. The high-strength degradable plastic film composition according to claim 1, characterized in that, In step (a) of the method for preparing plant-modified starch, the mass concentration of the starch emulsion is 30-50 wt%. The heating step is controlled at a temperature of 50±5℃.

3. The high-strength degradable plastic film composition according to claim 1, characterized in that, In step (b) of the method for preparing plant-modified starch, the amount of oxalic acid added is 15-20 wt% of the amount of starch used. The amount of the crosslinking aid added is 20-30 wt% of the amount of starch used.

4. The high-strength degradable plastic film composition according to any one of claims 1-3, characterized in that, In step (c) of the method for preparing plant-modified starch, the dispersant includes polyethylene glycol laurate. The amount of the dispersant added is 2-4 wt% of the amount of starch used.

5. The high-strength degradable plastic film composition according to any one of claims 1-3, characterized in that: The crosslinking agent includes diethylaminoethanol.

6. A high-strength degradable plastic film material, characterized in that, The high-strength degradable plastic film composition according to any one of claims 1-5 is used as a raw material for preparation.

7. A method for preparing the high-strength degradable plastic film material of claim 6, characterized in that, The process includes the steps of mixing selected amounts of the PBS, PPC, polycaprolactone, light-shielding and low-temperature resistant additive, crosslinking agent, and plant-modified starch, and the step of performing micro-crosslinking reactive extrusion on the resulting mixture.

8. The method for preparing the high-strength degradable plastic film material according to claim 7, characterized in that, The micro-crosslinking reactive extrusion step is performed using a twin-screw extruder; The temperature of the twin-screw extruder is controlled at 170-200℃, the feeding speed is 15-25 r / min, and the main extruder speed is 85-100 r / min.

Citation Information

Patent Citations

  • Preparation method of oxidation cross-linked esterification triple modified starch

    CN101045752A

  • Starch master batch for filling modification of degradable polymer material, and preparation method thereof

    CN109535490A

  • Full-biodegradable plastic mulching film, preparation method and application thereof

    CN112980153A